Handbook of lean manufacturing in the food industry - Dudbridge, Michael (USA : Blackwell, 2011)
"Lean manufacturing is a system that helps to reduce costs while improving performance and output quality. This book presents the principles of lean manufacturing as they can be applied to food manufacturing. Other books on this topic are written at a higher level and tend to attempt to shoehorn the principles of the car and consumer electronics industries into places where they do not really fit. This is the first book to apply lean principles specifically in food industry settings, offering solutions which can alleviate pressures currently facing the industry."--
"Lean manufacturing is a system that helps to reduce costs while improving performance and output quality. The techniques were initially developed in the automotive and engineering industries but are now being applied to a wide range of sectors including, increasingly, the food industry. The principle focus of lean manufacturing is to "work smarter, not harder". Through careful measurement of factory processes, causes of poor performance are identified and addressed. A variety of management tools and techniques can be used to control the activities of the business and to deliver the product and profits required. This book presents the principles of lean manufacturing as they can be applied to food manufacturing. Other books on this topic are written at a higher level and tend to attempt to shoehorn the principles of the car and consumer electronics industries into places where they do not really fit. This is the first book to apply lean principles specifically in food industry settings, offering solutions which can alleviate pressures currently facing the industry. Used as a handbook for managers, including at team leader / shift manager level, the book guides the reader through the steps that must be taken in order to successfully implement lean systems. It explores the various strategies suitable for different sectors of the industry and the various relationships along the food supply chain. This information can then be used to "sell" proposed changes to the wider workforce and help junior and middle managers implement and maintain the new practices. The book is suitable as a companion to training and education courses"--
Machine generated contents note: 1. Introduction to lean manufacturing in the food industry.a. Pressures in the food manufacturing industry.b. Alternative methods of lowering costs..2. First steps to lean manufacturing.a. The measurement of performance.b. Understanding the process of change.c. Encouraging action and improvement..3. Team work and the development of solutions.a. Solutions not problems.b. Continuous improvement.c. Leading effective teams..4. Starting to measure and quantify performance.a. Selection of KPIs (key performance indicators).b. Quality, availability and performance.c. Tracking performance. Record Keeping and the Score Card.d. Setting targets.e. Publicising good performance.f. The dashboard system for a clear business overview...5. Applying workplace organisation in the food industry.a. 5S systems of getting organised.b. Visual systems to help performance.c. Standard operation procedures..6. Improving flexibility and responsiveness.a. The use of casual labour.b. The can do attitude and positive thinking..7. Improving what we do.a. Process development.b. Value stream mapping.c. Reducing the processes that do not add value.d. Line balancing to optimise productivity..8. Improving how we do things.a. Making changes stick for all shifts.b. Improving communications.c. The learning factory..9. Planning the operation.a. Planning systems.b. The importance of sticking to plan.c. How to make the plan work..10. Start of shift meetings.a. Monitoring performance and actions.b. Where, when, who....c. Performance and action boards..11. The seven wastes in the food industry.a. Collecting information and opportunity spotting.b. The financial effects of eliminating waste.c. Designing processes to waste less.d. Energy and Water Usage.e. Quality management..12. How can we make the machines work better?.a. Total productive maintenance.b. Continuous improvement and minor modifications.c. Error proofing.d. Quick changeovers.e. Statistical process control..13. How can we let people contribute more?.a. Setting development plans.b. Training for increased performance.c. Selecting team members.d. Paperwork..14. How good are we?.a. Benchmarking.b. World class performance.
Includes index.
Includes bibliographical references and index.
Keywords: Food industry and trade -- Management -- Handbooks, manuals, etc; Food industry and trade -- Waste minimization -- Handbooks, manuals, etc; Lean manufacturing -- Handbooks, manuals, etc; TECHNOLOGY & ENGINEERING / Food Science